In-Band Full Duplex Wireless LANs: Medium Access Control Protocols, Design Issues and Their Challenges - Md. Ruhul Amin; Md. Shohrab Hossain; Mohammed Atiquzzaman (Information, 2020)
In-band full duplex wireless medium access control (MAC) protocol is essential in order to enable higher layers of the protocol stack to exploit the maximum benefits from physical layer full duplex technology. Unlike half duplex wireless local area network, a full duplex MAC protocol has to deal with several unique issues and challenges that arise because of the dynamic nature of the wireless environment. In this paper, we have discussed several existing full duplex MAC protocols and have shown qualitative comparisons among these full duplex MAC protocols. Full duplex in-band wireless communication has the potential to double the capacity of wireless network. Inter-client Interference (ICI) is a hindrance in achieving double spectral efficiency of the in-band full-duplex wireless medium. In this paper, we have classified existing solutions to the ICI problem and compared the solutions with respect to the proposed approaches, their advantages and disadvantages.We have also identified and discussed several issues and challenges of designing a full duplex MAC protocol. Results of qualitative comparisons of various wireless full duplex MAC protocols may be applied to design new protocols as well as researchers may find the identified issues and challenges helpful to solve various problems of a full duplex MAC protocol.